Childhood cancer mortality and survival in immigrants: A population‐based registry study in Finland. Issue 10 (24th August 2019) - Kyrönlahti, Anniina; Madanat‐Harjuoja, Laura; Pitkäniemi, Janne; Rantanen, Matti; Malila, Nea; Taskinen, Mervi
Abstract : Immigration in Europe has increased considerably over the past decades with the immigrant population similarly expanding in Finland. Our aim was to study childhood cancer mortality and survival in immigrants. In all, 4, 437 patients diagnosed with cancer under the age of 20 years between 1990 and 2009 were identified from the Finnish Cancer Registry and their parents from the Population Register Center. Information on demographic factors was obtained from Statistics Finland. Poisson regression modeling was used to estimate hazard ratios (HRs) for cancer deaths. The life table method and the log rank test were used in survival analysis. Patients or parents of foreign background and born abroad had higher 5‐year mortality (patient HR 2.03, 95% CI 1.18–3.49; maternal HR 2.11, 95% CI 1.46–3.04; paternal HR 1.85, 95% CI 1.29–2.66) compared to those of Finnish background and born in Finland. Childhood cancer survival in 5‐year follow‐up was higher if the mother (83% vs . 68%) or the father (83% vs . 70%) were of Finnish background and born in Finland. Despite equal access to public health care, we observed significant differences in childhood cancer mortality and survival by background. Cultural differences, linguistic obstacles and difficulties in navigating the health care system may contribute, along with genetic and biologic factors. Offering tailored information and taking cultural and linguistic aspects into account is necessary when diagnosing and treating patients from different ethnic backgrounds who have not yet integrated into the local culture and health care system. Abstract : What's new? Increasing immigration to Finland in recent decades has raised concerns about possible health gaps and health care disparities, particularly among children. The authors of this study, using data from the Finnish Cancer Registry, Population Register Center and Statistics Finland, investigated the effect of immigrant status specifically on childhood cancer mortality and survival. Among childhood cancer patients, mortality was found to be elevated for those born abroad and those with parents of foreign background. Mortality was influenced especially by maternal birth origin. Mortality differences between immigrants and native individuals were apparent six months after diagnosis and persisted two to four years later.